Penyuluhan Gigi Tiruan pada Lansia dan Pencegahan Denture Stomatitis - Sarahfin Aslan; Andy Fairuz; Andi Tenri Biba; Chusnul Chotimah (Idea Pengabdian Masyarakat, 2022)
The proportion of the elderly continues to grow throughout the world especially in developing countries. From the RISKESDAS data by Ministry of Health, it was found that the percentage of good and correct brushing behavior in the elderly age group was only 2.9%. So from many reports, it was found that many elderly people lost their teeth.In general, the function of teeth plays a role in the process of mastication, esthetics, and phonetics. The impact caused by tooth loss can affect the oral cavity and general or systemic health, so it is necessary to replace missing teeth. Many people who use dentures do not understand how to maintain their dentures. Dentures that are not properly cleaned can cause various negative impacts such as increased plaque accumulation and result in denture stomatitis and further tooth decay that affects the overall health of the oral cavity. Epidemiological data found that the incidence of denture stomatitis is 30-50% in removable denture users. In the initial survey, the majority of the Lanna sub-district community who joined the religious group" assembly were elderly and many did not realize the importance of using dentures and how to maintain good dentures. Based on this, it is necessary to conduct counseling. This service is carried out in the Lanna village community. The method we use is with lectures / animated video counseling, discussions, and questions and answers. The results of service, increased knowledge about the importance of dentures and correct denture maintenance to prevent denture stomatitis